PENURUNAN MUTU FISIK DAN KIMIA SUP LABU KUNING INSTAN YANG DIKEMAS MENGGUNAKAN ALUMINIUM FOIL - Fristy Azmi Asysyafa; Agus Suyanto; Nurrahman . (Universitas Muhammadiyah Semarang, 2025)
Instant pumpkin soup is an innovative food product that is practical and has high nutritional value. However, during storage, this product is prone to physical and chemical quality changes due to the influence of temperature and storage duration. This research aims to study the kinetics of the rate of physical and chemical deterioration of instant pumpkin soup packaged using aluminum foil during storage. Pumpkin was processed into soup, then packaged using aluminum foil, and stored at 27, 37, and 47°C for 0, 7, 14, 21, and 28 days. The research method was carried out with an experimental design using a 2-factor Completely Randomized Design (CRD), namely temperature and storage duration. Parameters observed included hygroscopicity, water activity (??), β-carotene content, and vitamin C content. The results showed that temperature and length of storage had a significant effect on changes in the physical and chemical quality of instant pumpkin soup. The temperature of 27°C is the best temperature in maintaining the quality of hygroscopicity, water activity (??), β-carotene, and vitamin C in the product.